Peran Bidhumas Polda Metro Jaya dalam Membangun Citra Positif Polisi Melalui Media Sosial Instagram - Rihhadatul 'Aisy; Moehammad Gafar Yoedtadi (Kiwari, 2022)
Instagram is a social media application that is currently widely used from the children, teenagers, and the most adult. In addition, instagram also used by agency of the government. Agency of the government can use social media application are very useful for building a positive image from the general public. One of the government agencies that uses the Instagram social media application is the Bidhumas Polda Metro Jaya (@humas.poldametrojaya). The purpose of the Bidhumas Polda Metro Jaya to create an Instagram account is to provide information related to appeals which are directives from the Kapolda, Kapolri, and the Government. On the other hand, they also want to make their audience the main consumers. And if the wider community gives a bad assessment of the image of the police agency in a case of a criminal act, such as a case of rape or harassment, it should only tarnish the name of the perpetrator who committed the crime and be given a sanction in accordance with the law that was violated. One of the roles of the Bidhumas Polda Metro Jaya in handling a case of other criminal acts that can happen to a member of the police is to bridge a relationship between all members of Polda Metro Jaya and the wider community and provide information that is transparent in accordance the code of ethics of public relations.Instagram merupakan salah satu aplikasi media sosial yang saat ini banyak digunakan oleh masyarakat dari kalangan anak-anak, remaja, hingga orang dewasa. Selain itu, instagram juga digunakan oleh beberapa instansi pemerintah untuk membangun sebuah citra positif, salah satunya ialah Bidhumas Polda Metro Jaya (@humas.poldametrojaya). Tujuan lembaga Bidhumas Polda Metro Jaya membuat akun Instagram ialah ingin memberikan informasi terkait imbauan-imbauan arahan dari Kapolda, Kapolri, dan Pemerintah. Di sisi lain, mereka juga ingin menjadikan khalayaknya sebagai konsumen utama. Dalam kasus lain adalah jika masyarakat luas yang memberikan penilaian buruk terhadap citra terhadap lembaga kepolisian pada sebuah kasus tindakan kriminal, seperti kasus pemerkosaan maupun pelecehan seharusnya hanya mencoreng nama oknum pelaku yang melakukan tindakan kriminal dan diberikan sebuah sanksi yang sesuai dengan undang-undang. Salah satu peran dari Bidhumas Polda Metro Jaya dalam menangani sebuah kasus tindakan kriminal lainnya ialah mejembatani sebuah hubungan antara Polda Metro Jaya dengan masyarakat luas serta memberikan informasi yang bersifat transparan dan sesuai dengan kode etik kehumasan.